Social representation of new foods among European students. Issue 12 (25th November 2014) - Mäkiniemi, Jaana-Piia; Bäckström, Anna; Ahola, Salla; Pieri, Michelle; Pirttilä-Backman, Anna-Maija
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to measure how three components of social representations (SRs) of new foods, Adherence to technology, Adherence to natural food, and Food as enjoyment, relate to Finnish and Italian university students' religiousness, country of origin, sex, and field of study. Design/methodology/approach – Italian and Finnish university students (n=564) completed a 27-item scale of SRs of new foods. A series of analysis of covariance was used to test the hypotheses. Findings – As expected, technology students scored higher on Adherence to technology than social science students, and women and religious persons scored higher on Adherence to natural food than men and non-religious persons. Unexpectedly, Finns scored higher on Food as an enjoyment than Italians. Originality/value – This study illustrates the usefulness of SR theory for studying food-related thinking, and throws more light on how religiousness, professional field, and sex are connected to the three components of SR of new foods in two European countries and food cultures.